Al-Kassaie's Position on Quranic Readings in his Book "Meanings in the Quran" (Journal of the College of Education for Women, 2023)
Thanks for All Mighty Allah creator of worlds and creating All Human Beings the Greatest Creator, and All Blessings for the Latest Messenger Mohammed and all his Good family. Holly Quran is considered the very purified phrases and the very corrective words at all, within its readings representing the real aspect of Arabic Grammar by which a reflex to be depended to be the basic of holding the complete and the full of Arab Language. In this context, I studied the point of view of Al Kassaie in writing the meanings of Holly Quran, that Book which was lost and had rewritten by Dr. Essa Shuhata. DR. Mahmood Fahmi Al Hujazi in his introduction for this Book after its scripts were deleted, that work represented a work that discovered a lost thing, it presented a book has description related to ancient time. The current research has an introduction addressed by the attitude of ancient towards Holly Quran readings additionally to three main chapters , the first chapter includes methods of AL KASAIE in Holly Quran readings , but the second chapter includes addresses by the attitude of AL KASAIE towards Holly Quran readings, but the third chapter includes and addressed by Samples of criticizing of AL KASAIE in correct Quran readings . After that I ended my research with several conclusions I mentioned to at the last of my own research.